Downregulation of Filamin a Expression in the Aorta Is Correlated With Aortic Dissection - Chen, Yue; Wei, Xiang; Zhang, Zihao; He, Yi; Huo, Bo; Guo, Xian; Feng, Xin; Fang, Ze-Min; Jiang, Ding-Sheng; Zhu, Xue-Hai (Frontiers in Cardiovascular Medicine, 2021)
Filamins (FLNs) are actin cross-linking proteins, and as scaffolding proteins, FLNs are closely associated with the stabilization of the cytoskeleton. Nevertheless, the biological importance of FLNs in aortic dissection (AD) has not well elucidated. In this study, we first reanalyzed datasets downloaded from the Gene Expression Omnibus (GEO) database, and found that in addition to the extracellular matrix, the actin cytoskeleton is a key structure associated with AD. Given that FLNs are involved in remodeling the cytoskeleton to affect cellular functions, we measured their expression levels in the aortas of patients with Stanford type A AD (TAAD). Our results showed that the mRNA and protein levels of FLNA were consistently decreased in dissected aortas of both humans and mice, while the FLNB protein level was upregulated despite decreased FLNB mRNA levels, and comparable expression levels of FLNC were observed between groups. Furthermore, the immunohistochemistry results demonstrated that FLNA was highly expressed in smooth muscle cells (SMCs) of aorta in non-AD samples, and downregulated in the medial layer of the dissected aortas of humans and mice. Moreover, we revealed that FOS and JUN, forming a dimeric transcription factor called AP-1 (activating protein-1), were positively correlated with the expression of FLNA in aorta. Either overexpression of FOS or JUN alone, or overexpression of FOS and JUN together facilitated the expression of FLNA in primary cultured human aortic SMCs. In the present study, we not only detected the expression pattern of FLNs in aortas of humans and mice with or without AD, but also found that the expression of FLNA in the AD samples was significantly reduced and that AP-1 might regulate the expression of FLNA. Our findings will contribute to the elucidation of the pathological mechanisms of AD and provide potential therapeutic targets for AD.